Menghidupkan Nilai Sosial dalam Pembelajaran IPAS: Peran Guru dan Dinamika Kelas di SD Negeri Mantren - Agoes Hendriyanto; Halima Wahyu Pratama; Salsa Bila Nabila (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to analyze the implementation of social values in the teaching of Natural and Social Sciences (IPAS) at SD Negeri 1 Mantren. Using a qualitative approach, the data sources consist of 6 teachers, 1 educator, and 30 students. The IPAS learning process at SD Negeri 1 Mantren shows that teachers are quite well-prepared in designing and delivering material, although hindered by the limited availability of adequate learning media. The learning process remains less varied and has not fully accommodated the diverse characteristics of students. IPAS learning at SD Negeri 1 Mantren has successfully instilled social values such as cooperation, tolerance, responsibility, and empathy. Teachers demonstrate preparedness through the development of lesson plans and mastery of the material, despite the limitations in facilities. Positive feedback encourages student enthusiasm during discussions. Group activities contribute to increased social awareness and the application of values in everyday life. However, individual approaches and emotional support are still needed for students who lack confidence.Overall, the IPAS learning process is capable of shaping students’ social character by linking the material to real-life contexts relevant to them. These findings imply the need for developing more effective and student-centered teaching practices.